Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions. I: a case study of leaf development and seasonal variation of photosynthetic capacity in Quercus robur (L.), Q. ilex (L.) and their semidecidu - Both, Holger; Brüggemann, Wolfgang (Trees, 2009)
Leaf development of Quercus robur (deciduous), Q. ilex (evergreen) and of their hybrid Q. 9 turneri was assessed under Central European climate conditions. In all three taxa, development of maximum photosynthetic capacity was slow, although whole chain electron transport, grana development, the xanthophyll cycle and the biochemical capacity for photosynthesis were already completely present at day 7 after budbreak (DAB 7). In the course of the following 30 days, shifts in the levels of metabolites of the photosynthetic dark reactions were observed, indicating a change from ribulose bisphosphate (RubP) regeneration limitation towards RubP consumption limitation of photosynthesis. At the same time, electron transport rates had strongly increased and the capacity of the light reactions did not seem to limit photosynthesis. Sucrose levels in the leaves increased strongly, indicating sink limitation of photosynthesis, which might be responsible for the observed slow development of maximum photosynthetic capacity in all three taxa.
Keywords: á; leaf development; leaf development á quercus; photosynthesis; Quercus; Sink limitation; sink limitation á photosynthesis